Literatura, teatro e inteligencia artificial, de José Romera Castillo (ed.) (Castilla. Estudios de Literatura, 2026)
Review of the book Literatura, teatro e inteligencia artificial (Madrid, Verbum, 2026), by José Romera Castillo (ed.).The collective volume Literatura, teatro e inteligencia artificial, edited by José Romera Castillo and published by Verbum in 2025, brings together twenty contributions from researchers at Spanish, European and American universities on the impact of artificial intelligence on literary creation and the performing arts. Organized into three thematic sections —general legal and theoretical aspects, literature and AI, and theatre and AI—, the volume addresses questions such as algorithmic authorship, AI-assisted literary translation, poetry generation and the incorporation of digital technologies into contemporary dramaturgy. The collection more than fulfils its purpose: not to describe the phenomenon from a distance, but to situate itself within it and think from there.